Activation of Endoplasmic Reticulum Stress and Unfolded Protein Response in Congenital Factor VII Deficiency - Andersen, Elisabeth; Chollet, Maria Eugenia; Myklebust, Christiane Filion; Pinotti, Mirko; Bernardi, Francesco; Chuansumrit, Ampaiwan; Skarpen, Ellen; Sandset, Per Morten; Skretting, Grethe (Thrombosis and Haemostasis, 2018)
Congenital factor (F) VII deficiency is a bleeding disorder caused by a heterogeneous pattern of mutations in the F7 gene. Protein misfolding due to mutations is a strong candidate mechanism to produce the highly represented type I FVII deficiency forms, characterized by a concomitant deficiency of FVII antigen and activity. Misfolded proteins can accumulate within the endoplasmic reticulum (ER) causing ER stress with subsequent activation of the unfolded protein response (UPR). So far, there are limited data on this important issue in FVII deficiency. In this study, we chose as candidate FVII model mutations, the p.Q160R, p.I289del and p.A354V-p.P464Hfs, which are all associated with severe to moderate type I FVII deficiency. In vitro expression of the recombinant (r) mutants rFVII-160R, rFVII-289del or rFVII-354V-464Hfs, which are characterized by either amino acid substitution, deletion, or by an extended carboxyl terminus, demonstrated inefficient secretion of the mutant proteins, probably caused by intracellular retention and association with ER chaperones. Both ER stress and UPR were activated following expression of all FVII mutants, with the highest response for rFVII-289del and rFVII-354V-464Hfs. These data unravel new knowledge on pathogenic mechanisms leading to FVII deficiency, and support the investigation of pharmaceutical modulators of ER stress and UPR as therapeutic agents.
Keywords: factor VII deficiency; endoplasmic reticulum stress; unfolded protein response